The enhancement of teaching and learning through blended learning and collaborative co-lecturing - Perera, Corinne Jacqueline; Chua, Yan Piaw; Asirvatham, David; Zainuddin, Zamzami; Harris, Alma; Jones, Michelle (2017)
Instructors of higher education institutions often explore new methods of teaching using innovative techno-pedagogical approaches. Co-lecturing with colleagues having similar expertise, may prove to be just the answer to create a more inviting learning environment. The present study reports on postgraduate students' perceptions of the teaching-learning blended mode of delivery, co-taught by two lecturers' concurrently in the 'Qualitative Research' elective offered at the Institute of Educational Leadership, University of Malaya. A predominantly qualitative research methodology was adopted for data collection and analysis, with students' comments, feedback, and reflections captured through Padlet. Results indicate that students have very positive perceptions of their experiences through blended learning co-lectures. Students particularly va lued the use of class time for both hands-on and online activities that enabled an interactive, knowledge-sharing classroom experience with both lecturers present. Exposure to various teaching-learn ing styles, allowed for a more interpersonal relationship with their peers and lecturers, gained through active learning teaching techniques. The findings of this action research study provide the opportunity for lecturers to draw on students' feedback and adapt their teaching practices to provide meaningful and personalized learning experiences for all students through a collaborative co-lecturing mode of delivery.